Proliferation and osteogenic differentiation of amniotic fluid-derived stem cells - Muduli, Saradaprasan; Lee, Henry Hsin-Chung; Yang, Jia-Sin; Chen, Ting-Yeh; Higuchi, Akon; Subbiah, Suresh Kumar; Alarfaj, Abdullah A.; Murugan, A. Munusamy; Benelli, Giovanni; Murugan, Kadarkarai; Liu, Ching-Yuan; Chen, Yi-Fan; et al. (Royal Society of Chemistry, 2017)
Human amniotic fluid-derived stem cells (hAFCs) are pluripotent fetal cells capable of differentiating into multiple lineages, including cell types of each of the three embryonic germ layers. Proper differentiation and maintenance of pluripotency, the defining characteristics of stem cells, are regulated not only by the cells themselves but also by their microenvironment. Furthermore, the physical characteristics of the cell culture materials, such as material elasticity, influence the results of stem cell differentiation. We investigated the osteogenic differentiation efficiency of hAFCs cultured on cell culture materials with different elasticities that were grafted with extracellular matrix-derived oligopeptides. Polyvinyl alcohol-co-itaconic acid (PV) hydrogels with different elasticities were prepared by controlling the crosslinking intensity, and the resulting PV hydrogels were grafted with and without extracellular matrix (ECM)-derived oligopeptides. Specific ECM-derived oligopeptides were used to maintain the pluripotency of AFCs and were determined by evaluation of pluripotent gene expression (Sox2 and Oct4). The osteogenic differentiation efficiency of the hAFCs, cultured on PV hydrogels grafted with and without ECM-derived oligopeptides, was analyzed by alkaline phosphatase activity, Alizarin Red S staining, and von Kossa staining. Unmodified PV hydrogels induced osteoblast differentiation of hAFCs with high efficiency. We conclude that the hAFCs interacting with ECM-derived oligopeptides tended to maintain an undifferentiated state.